PENGARUH PROFITABILITAS DAN ISLAMIC SOSIAL REPORTING TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI INDEK SAHAM SYARIAH INDONESIA TAHUN 2018 2021 - Yoga Pangestu; Maulana Yusuf; Firman Syah Noor (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
This research is entitled Factors Influencing Public Interest in Performing Umrah Worship During the Covid-19 Pandemic (Case Study of Hajj and Umrah Travel at PT. Ameera Mecca, Batang Hari Regency). The aims of this study are: 1) To find out the factors that influence the community's interest in organizing the Umrah pilgrimage at PT. Ameera Mecca during the pandemic. 2) To determine the influence of these factors partially and simultaneously on public interest in organizing the Umrah pilgrimage at PT. Ameera Mecca during the pandemic. 3) To find out what factors have the most dominant influence on people's interest in organizing the Umrah pilgrimage at PT. Ameera Mecca during the pandemic. The research method used by researchers is a quantitative approach. The results of this study are: 1) From the results of the regression test it was found that partially the product had a significant effect on public interest in performing Umrah during the Covid 19 period at Ameera Tour and Travel Batanghari. 2) From the results of the regression test it was found that partially the service had a significant effect on community interest in performing the Umrah pilgrimage during the Covid 19 period at Ameera Tour and Travel Batanghari. 3) From the results of the regression test it was found that partially Promotion had no significant effect on Community Interest in performing the Umrah pilgrimage during the Covid 19 period at Ameera Tour and Travel Batanghari. 4) From the results of the regression test it was found that partially the price did not have a significant effect on public interest in performing the Umrah pilgrimage during the Covid 19 period at Ameera Tour and Travel Batanghari. 5) Simultaneously, Products, Services, Promotions and Prices have a significant effect on Community Interest in performing the Umrah pilgrimage during the Covid 19 period at Ameera Tour and Travel Batanghari.